2014
DOI: 10.1021/ac402916v
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystal-Based Proton Sensitive Glucose Biosensor

Abstract: A transmission electron microscopy (TEM) grid filled with 4-cyno-4-pentylbiphenyl (5CB) on the octadecyltrichloro silane-coated glass in an aqueous medium was developed to construct a glucose biosensor by coating poly(acrylicacid-b-4-cynobiphenyl-4-oxyundecylacrylate) (PAA-b-LCP) at the aqueous/5CB interface and immobilizing glucose oxidase (GOx) covalently to the PAA chains. The glucose was detected from a homeotropic to planar orientational transition of 5CB by polarized optical microscopy under crossed pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 36 publications
(64 reference statements)
0
55
0
Order By: Relevance
“…Because of their high sensitivity and rapid response with respect to orientation, small-molecule LCs are an attractive medium for detecting chemical/biochemical events occurring at an interface as a result of optical changes that can be viewed with the aid of a polarized optical microscopy [28][29][30][31]. An optical change can occur as a result of a change in orientation of the LCs from vertical to parallel alignments at the water/LC interface upon adsorption of biomaterials [32].…”
Section: Introductionmentioning
confidence: 99%
“…Because of their high sensitivity and rapid response with respect to orientation, small-molecule LCs are an attractive medium for detecting chemical/biochemical events occurring at an interface as a result of optical changes that can be viewed with the aid of a polarized optical microscopy [28][29][30][31]. An optical change can occur as a result of a change in orientation of the LCs from vertical to parallel alignments at the water/LC interface upon adsorption of biomaterials [32].…”
Section: Introductionmentioning
confidence: 99%
“…Formation of LC droplets was carried out using the same method previously reported by Khan et al [24]. Briefly, the liquids were supplied to a microfluidic device via a flexible plastic tubing (Norton, USA, I.D.…”
Section: Cb Paa Droplet Formation and Its Biotinylationmentioning
confidence: 99%
“…Previous studies have revealed that the response of 5CB can be tuned to external stimuli by functionalizing it with surfactant and polyelectrolytes [19,20]; for example, 5CB functionalized with pH-responsive poly(acrylic acid) (PAA) brushes as a support for immobilization of glucose oxidase has been used as a glucose biosensor. This sensor showed improved sensitivity in glucose detection as a result of the fast response of 5CB to changes in the local pH caused by the enzymatic reaction of glucose [21]. Similarly, a cholesterol oxidase (ChO)-immobilized LC/aqueous interface, with co-immobilization of horseradish peroxidase (HRP), can be used as a cholesterol biosensor, based on a similar enzymatic reaction.…”
Section: Introductionmentioning
confidence: 99%